2022
DOI: 10.1002/jmr.2983
|View full text |Cite
|
Sign up to set email alerts
|

Purification, biochemical characterization, and DPP‐IV and α‐amylase inhibitory activity of Berberine from Cardiospermum halicacabum

Abstract: Diabetes mellitus (DM) has spread across the globe, increasing the risk of obesity, cardiovascular disease, and other comorbidities. Despite substantial research into the development of diabetic treatments that are effective in lowering blood glucose levels, their efficiency is short‐lived due to unpleasant side effects such as weight gain and hypoglycemia. The discovery of secondary metabolites in the prevention and treatment of diabetes and its complications has an incentive to take interest in plant‐based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…α‐Amylase and α‐Glucosidase are crucial enzymes that break down starch into simpler sugars in the human body. α‐Amylase s hydrolyses complex polysaccharides into oligosaccharides and disaccharides, which are then hydrolysed by α‐Glucosidase into monosaccharides absorbed into the hepatic portal vein to increase postprandial glucose levels (Naik et al ., 2022). Inhibiting carbohydrate‐digesting enzymes such as α‐Amylase and α‐Glucosidase in gastrointestinal glucose absorption, which lower postprandial glucose levels, is used to manage diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…α‐Amylase and α‐Glucosidase are crucial enzymes that break down starch into simpler sugars in the human body. α‐Amylase s hydrolyses complex polysaccharides into oligosaccharides and disaccharides, which are then hydrolysed by α‐Glucosidase into monosaccharides absorbed into the hepatic portal vein to increase postprandial glucose levels (Naik et al ., 2022). Inhibiting carbohydrate‐digesting enzymes such as α‐Amylase and α‐Glucosidase in gastrointestinal glucose absorption, which lower postprandial glucose levels, is used to manage diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…The Rg level of ADP 3 fluctuated between 26.8 and 27.2 Å, while csADP2 showed a fluctuation between 26.9 and 27.3 Å. These fluctuations were slightly lower compared to several previous studies [55,56]. Moreover, the number of hydrogen bonds was also considered to examine the dynamic equilibration of the complex system.…”
Section: Molecular Dynamics Stimulationmentioning
confidence: 94%
“…Similarly, another known alkaloid, berberine (Figure 9b), was isolated from the Cardiospermum halicacabum plant and found to retard the activity of α-amylase by 72% at 10 μg/mL. In addition, in silico investigations indicated that berberine adheres to the enzyme's active site [156]. Another class of bioactive molecules, xanthones named garcixanthone D and garcinone E (Figure 9c), were purified from the pericarp of Garcinia mangostana and showed 93.8 and 85.6% inhibition against α-amylase, respectively.…”
Section: Miscellaneous Secondary Metabolites As α-Amylase Inhibitorsmentioning
confidence: 95%
“…Similarly, another known alkaloid, berberine ( Figure 9 b), was isolated from the Cardiospermum halicacabum plant and found to retard the activity of α-amylase by 72% at 10 μg/mL. In addition, in silico investigations indicated that berberine adheres to the enzyme’s active site [ 156 ].…”
Section: Secondary Metabolites Isolated From Various Plant Sources As...mentioning
confidence: 99%